Сonsolidation and creepof subfoundations having finite widths КОНСОЛИДАЦИЯ И ПОЛЗУЧЕСТЬ ОСНОВАНИЙ ФУНДАМЕНТОВ КОНЕЧНОЙ ШИРИНЫ - Ter-Martirosyan Zaven Grigor’evich (Vestnik MGSU, 2013)
The authors formulate and solve the problem of consolidation and creep of saturated clay subfoundations exposed to localized loads (the two-dimensional problem formulation). The findings have proven that, if the two-dimensional problem is considered, any excessive pore pressure is concentrated immediately under the area exposed to the localized loading, and it penetrates into the depth equal to 1/2 of the strength of the compressed width. Subfoundation subsidence is caused by both shear and 3D deformations of soil. Besides, the ratio of shear-to-3D deformations reaches 10. Therefore, the authors propose to represent the subfoundation subsidence as the sum of shear and 3D deformations.The differential equation of the filter consolidation, if considered as the 2D problem, is solved using the Mathcad software. The software is used to analyze the isolines of excessive pore pressure at any moment following the loading application. New depen- dence representing the ratio of the changing area of the diagram of the average effective tension to the area of the diagram of the average tension in the stabilized condition is proposed by the authors.In the final section of the article, the authors solve the problem of prognostication of the subsidence pattern for the water saturated subfoundation with account for the shear creep of the soil skeleton. The authors employ the visco-elastic Bingham model characterized by time-dependent viscosity ratios. The authors have proven that in this case the subsidence following the shear load will develop as of the moment of application of the external load pro rata the logarithm of time irrespectively of the process of filtration consolidation. Приведены постановка и решения задач консолидации и ползучести водонасыщенных оснований из глинистых грунтов под воздействием местной нагрузки (плоская задача). Показано, что в условиях плоской задачи избыточное поровое давление в начальный момент нагружения локализуется непосредственно под местной нагрузкой на глубину 1/2 от мощности сжимаемой толщи и затем смещается вниз во времени и что осадка основания обусловлена как сдвиговыми, так и объемными деформациями грунта. Кроме того, соотношение сдвиговых и объемных частей достигает 10. Поэтому предложено осадку основания определить в виде суммы от объемных и сдвиговых деформаций в отдельности.Для решения дифференциального уравнения фильтрационной консолидации в условиях двухмерный задачи используется программный комплекс Mathcad. Это позволило производить расчеты по определению изолиний избыточного порового давления для любого момента времени от начала приложения нагрузки. Для определения степени консолидации осадки предложена новая зависимость в виде отношений изменяющейся площади эпюры среднего эффективного напряжения к площади эпюры среднего напряжения в стабилизированном состоянии.В заключительном разделе статьи приведено решение задачи по прогнозированию осадки водонасыщенного основания с учетом сдвиговой ползучести скелета грунта. В качестве расчетной принята упруго-вязкая модель Бингама с изменяющимися во времени коэффициентами вязкости. Показано, что в этом случае сдвиговая часть осадки с момента приложения внешней нагрузки будет развиваться пропорционально логарифму времени независимо от процесса фильтрационной консолидации.